OPTIMALISASI KETERSEDIAAN AIR BERSIH DAN PENINGKATAN KUALITAS LINGKUNGAN MELALUI BUDIDAYA MAGGOT DAN SISTEM AIR BERSIH LAYAK MINUM RO DI DESA SUNGGINGAN, KEC MIRI, KAB SRAGEN - Anggel, Leony Anggel Damayanti; Aksal Hoer Nurajam; Huda Nur Aziz; Muhammad Sayidina Irzhy; Muhammad Mufid Haidar; Noah Presleyn Norel; Rafi Hakiim Nur Arief; Wahyu Dwi Handana; Zikra Hafizah; Wahyu Tri Utomo (CV SWA Anugerah, 2025)
Sunggingan Village is a village located in Miri District, Sragen Regency, with an altitude of 115 meters above sea level. This village is about 7 km to the southwest of Mount Kemukus. To the north, Sunggingan Village borders Brojol Village, while to the east it borders Girimargo Village. The southern part of this village borders Jeruk Village, while on the west side it borders Boyolali Regency. Sunggingan Village has an area coverage of 300 ha led by 2 hamlet heads, namely Mas Aziz, which is divided into 4 hamlets, namely Bulaksari (RT 02 and 20), Bulakrejo, Pondok (RT 03), and Pilangsari (RT 04 and 05) . Based on the statement above, the KKN 203 UNS team carried out three work programs, namely maggot cultivation, a clean water system suitable for RO drinking, and construction of reservoirs to optimize the availability of clean water. Real Work Lecture activities carried out by the UNS KKN 203 team started from 9 July to 22 August 2024. This activity went well thanks to the participation of the community in Sunggingan Village, Miri District, Sragen Regency. The aim of the success of the work program that has been implemented by the KKN 203 UNS team is to educate the community about the urgency of the drought problem that occurred in Sunggingan Village, develop community creativity in increasing the potential for making new modern technologies, and optimize the technology that will be created by considering the driving factors. and obstacles in the manufacturing process.